CHARACTERISTICS OF PURE LANDRACE MEAT MARINEED IN VARIOUS NATURAL MATERIAL EXTRACTS - N. Md. N., Hermawati; Miwada, I N.S; Lindawati, S. A. (Jurnal Peternakan Tropika, 2019)
This study aims to analyze the ability of garlic extract, onion, pineapple and turmeric as antibacterial and its effect on the characteristics of landrace pork. The research method used a completely randomized design namely garlic (P1), shallots (P2), pineapple (P3) and turmeric (P4) with 4 replications. The variables measured included pH, water content, water binding capacity, color, aroma and total bacteria. Data analysis using variance (Anova) and non-parametric (Kruskal-Wallis). The results showed that the pH value of landrace pork with turmeric extract (6.67%) significantly (P <0.05) was higher than that of garlic extract (5.61%), shallots (5.45%) and pineapple (5.54%). The ability of binding capacity of meat with red onion extract (27.77%) had a significant effect (P<0.05) higher than garlic extract (26.53%), pineapple (26.19%) and turmeric (22.56%). The panelists response to the color of landrace pork had a significant effect (P<0.05) on turmeric extract. However, it has no significant effect (P>0.05) on garlic extract, onion and pineapple. The total bacteria of landrace pork with garlic extract (3,3 x 10 8 CFU/g) and shallots (3,8 x 10 8 CFU/g) significantly affected (P<0.05) lower than pineapple extract (4.6 x 10 8 CFU/g) and turmeric extract (4.6 x 10 8 CFU/g). Water content and aroma of landrace pork from the four extracts of natural ingredients showed no significant difference. The conclusion of this study is the ability of antibacterial bioactive substances from the four natural extract ingredients to show that garlic and shallot extract has a significant effect compared to pineapple extract and turmeric extract. Keywords: natural ingredient extract, marination, pork